2015
DOI: 10.1109/tit.2015.2490066
|View full text |Cite
|
Sign up to set email alerts
|

The Second-Order Coding Rate of the MIMO Quasi-Static Rayleigh Fading Channel

Abstract: The second-order coding rate of the multiple-input multiple-output (MIMO) quasi-static Rayleigh fading channel is studied. We tackle this problem via an information-spectrum approach and statistical bounds based on recent random matrix theory techniques. We derive a central limit theorem (CLT) to analyze the information density in the regime where the block-length n and the number of transmit and receive antennas K and N , respectively, grow simultaneously large. This result leads to the characterization of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 23 publications
5
43
0
Order By: Relevance
“…Our large deviation result is valid for all normalized rates 0 < r < r erg . When we evaluate the error exponent for small |r erg − r| ≪ 1, our results match with the upper bound obtained by [9]. While the asymptotic limit of large antenna numbers is somewhat idealized, it is known from other works, e.g.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our large deviation result is valid for all normalized rates 0 < r < r erg . When we evaluate the error exponent for small |r erg − r| ≪ 1, our results match with the upper bound obtained by [9]. While the asymptotic limit of large antenna numbers is somewhat idealized, it is known from other works, e.g.…”
Section: Introductionsupporting
confidence: 83%
“…These results are of a central-limittheoretic nature, in that they are valid for large blocklengths with the rate converging to the ergodic rate at a fixed error probability. Similar results were obtained for MIMO systems in [9], where the number of antennas also goes to infinity at a fixed ratio with T . In contrast to the Gallager bound this approach does not capture the tails of the error probability, i.e.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…The codewords satisfy the power constraint 3 2 The assumption that H and W take on independent realizations over successive coherence intervals is critical for the results obtained in this paper, namely, Proposition 1 in Section IV and the saddlepoint expansions presented in Section V that follow from it. In contrast, the assumption that H is zero-mean Gaussian is not critical since Proposition 1 applies to any fading distribution for which (17) and (18) are satisfied. 3 While in the information and communication theory literature, it is more common to impose a power constraint per codeword X L , practical systems typically require a per-coherence-interval constraint.…”
Section: System Modelmentioning
confidence: 99%
“…Indeed, it can be shown that the family of random variables (29) implies that the first condition (17) required for Proposition 1 and Corollary 2 is satisfied. Regarding the second condition (18), it can be observed that V s (ρ)…”
Section: Theorem 3 (Saddlepoint Expansion Rcu S )mentioning
confidence: 99%